Effect of increased nitrogen depositions and drought stress on the development of Scots pine (Pinus sylvestris L.) - II. Root system response - E. Palátová (Journal of Forest Science, 2002)
Effects of drought stress, stress by increased nitrogen depositions and combined effect of the two stress factors on the growth of Scots pine (Pinus sylvestris L.) were studied in two experimental series in 1994-1997. The drought stress was induced by reduction of atmospheric precipitation by 60%, the increased nitrogen depositions were simulated by repeated applications of ammonium sulphate at a dose corresponding to 100 kg N/ha per year. All stress factors under study impacted the biomass, vertical distribution, functionality and mycorrhizal infection of fine roots. The root system responded to simulated stresses as early as from the very first year of their effect exhibiting greater damage than the above-ground part of the plant (see PALÁTOVÁ 2001).